RESERVES FOR WAR CONTINGENCIES AND POSTWAR ADJUSTMENTS. - Miller, Herbert E. (The Accounting Review, 1944)
Abstract The purpose of periodic financial statements of a corporation is to furnish information that is necessary for the formulation of dependable judgments. Even in normal times this is a substantial challenge to accountants, considering the complexity of the corporate system. During a period when the entire business economy is geared to the exigencies of total war, the task of preparing accounting statements adequate for the formulation of dependable judgments assumes immense proportions. The current popularity of provisions for war contingencies and postwar adjustments or some such titled reserve seems to invite a review of this practice. Its popularity is disclosed in a study by the Research Department of the American Institute of Accountants reported in the November, 1943, "Journal of Accountancy." And since such reserve provisions may accomplish or at least open the way for-profit-smoothing, perhaps a review of "accepted" practice in this area of accounting is justified. In this paper the concern will be with general accounting theory and practice and will not include the problem of tax policy in relation to postwar conversion expenditures.